HRD INTERVENTION IN VEGETABLE AND FRUIT PROMOTION COUNCIL KERALAM (VFPCK) WITH SPECIAL EMPHASIS ON TRAINING PROGRAMS - Sreekumar V.N
Unknown to many, one of India’s most successful agriculture development projects is being run in Kerala. Its activities and achievements put to shame much of what our state agriculture departments in this country have been doing since Independence. In VFPCK, a number of HRD intervention programs have been providing four competency developments. Among them, training is important. They have separate department for training. As a profit making organization, VFPCK wants to improve its services. But it has so many drawbacks in providing training. They are providing training in the traditional way. They have no proper mechanism for identifying the training needs. Again, they didn’t assess the impact of training in the organizational and field level. They have been conducting the training in usual way and didn’t make any scientific intervention upon it.